What differentiates youths who use e-cigarettes from those who smoke traditional tobacco products? - Hugo Torregrossa; Bertrand Dautzenberg; Pierre Birkui; Nicole Rieu; Marie-Dominique Dautzenberg; Maria Melchior; Murielle Mary-Krause (BMC, 2022)
Abstract Background Electronic cigarette (e-cigarette) use has spread among adolescents in many countries, however users' characteristics are not well known. We aimed to compare characteristics of exclusive e-cigarette users to those of exclusive tobacco users and dual users. Methods Data come from a representative sample of 11-19 years old students in Paris, surveyed each year between 2013 and 2017. Current e-cigarette and tobacco use were ascertained in the preceding 30 days. Data were analyzed using random intercept multinomial logistic regression models, exclusive tobacco smokers being the reference group. Results Among the 17,435 students included, 2.3% reported exclusive e-cigarette use, 7.9% exclusive tobacco use and 3.2% dual e-cigarette and tobacco use. Compared to exclusive tobacco smokers, e-cigarette users were: a) less likely to use cannabis (adjusted Odds-Ratio (aOR) = 0.15, 95% confidence interval (95% CI) = 0.09-0.25); b) more likely to initiate smoking with an e-cigarette or a hookah rather than traditional cigarettes (aOR = 2.91, 95% CI = 1.74-4.87 and aOR = 15.99, 95% CI = 8.62-29.67, respectively). Additionally, exclusive e-cigarette users are younger with an aOR = 0.29 (95% CI = 0.17-0.49) among 13-15 years and aOR = 0.11 (95% CI = 0.06-0.21) among > 17 years as compared to 11-13 years. The probability of being an exclusive e-cigarette user is lower among participants whose best friend smokes tobacco (aOR = 0.30, 95% CI = 0.20-0.44). Exclusive tobacco users and dual users have similar profiles. Conclusions Adolescents who only used e-cigarettes had intermediate levels of risk compared to nonusers and those who used tobacco and/or e-cigarettes, suggesting that e-cigarettes use extends to young people at low-risk of using tobacco products.